Kelembagaan dan Bauran Pemasaran Hasil Tangkapan Nelayan di Tempat Pelelangan Ikan (TPI) Desa Sumberanyar Kecamatan Paiton Kabupaten Probolinggo - Susilowati, Susilowati; Purwandhini, Ari Septianingtyas (KUBIS, 2022)
Research on institutions and marketing of fishermen's catches at fish auctions. The background of this research is to introduce TPI Paiton to the community, to increase fishermen's income and fishermen's welfare in Sumberanyar Village, Paiton District, Probolinggo Regency. The purpose of this research is to determine the level of utilization and the need for basic facilities, functional facilities, and supporting facilities. To find out the application of 4P in the process of selling fish at TPI Paiton, Sumberanyar Village, Paiton District. The research was conducted in Paiton District using the Slovin method. The analytical method used is a qualitative approach. The results of the discussion showed that the condition of the facilities at TPI Paiton, both basic facilities, functional facilities, and supporting facilities were still all functioning and used by fishermen. The application of 4P at TPI Paiton is product, where the products at TPI Paiton are salted fish and fresh fish, then the price or price where the price set by traders at TPI Paiton is based on the purchase price of fish per kilo and customer prices. Place or a place where the place offered by the producer is still only a few places such as traditional markets, out of town, factories, and in their own homes. Promotions or promotions carried out at TPI Paiton have been effective by selling fish in traditional markets, outside the city, factories and in their own homes.